Therapeutic potential of the neutralizing monoclonal antibody 45G3 against encephalomyocarditis virus - Yanfang Zhang; Zhiying Wang; Yaohui Fang; Qiong Zhu; Jie Fu; Sijing Hu; Jiayin Jin; Min Zhou; Xijia Liu; Danna Zhang; Shouwei Huang; Yali Deng; et al. (Animal Diseases)
Abstract Encephalomyocarditis virus (EMCV), a potential zoonotic pathogen, poses significant socioeconomic and public health challenges across various host species. Although EMCV rarely triggers severe clinical symptoms in humans, its widespread prevalence and unique biological characteristics underscore the need for continuous surveillance and the development of effective therapeutics and prophylactics. In this study, we evaluated the neutralizing effects of a monoclonal antibody derived from the spleens of mice immunized with EMCV virus-like particles (VLPs), both in vitro and in vivo. Using recombinant DNA technology, we engineered a baculovirus system to express EMCVs P12A and 3C, facilitating the production of VLPs in Sf9 cells. These VLPs serve as antigens to immunize mice, leading to the isolation of the monoclonal antibody 45G3. This antibody exhibited high specificity for EMCV conformational epitopes, excluding linear epitopes, and demonstrated potent in vitro neutralizing activity, with an IC50 of 0.01873 μg/mL. Immunoelectron microscopy (IEM) revealed a strong direct interaction between the 45G3 antibody and EMCV particles. Virus adsorption inhibition assays demonstrated that 45G3 effectively blocked viral attachment, thereby preventing further infection of host cells. These findings further support the notion of a robust interaction between the virus and the antibody. Moreover, in vivo assessments revealed that 45G3 significantly reduced viral loads in treated mice and improved survival outcomes following EMCV exposure. Additionally, posttreatment analysis revealed reduced tissue damage and a markedly decreased inflammatory response in the brain, indicating that the 45G3 antibody effectively blocked viral infection, thereby mitigating tissue damage and enhancing survival. These findings position 45G3 as a promising candidate for EMCV management and provide a strong foundation for the future development of antiviral drugs targeting this widespread virus.